Practice of Granting Remission for Corruption Convicts Based on the Perspective of Human Rights and the Effectiveness of Corruption Eradication - Rezky Pratama; Evita Isretno Israhadi (Jurnal Multidisiplin Indonesia, 2025)
This study examines the practice of granting remissions to corruption convicts from a human rights (HAM) perspective and its effectiveness in eradicating corruption in Indonesia. Granting remissions, as a form of correctional policy, often reaps controversy, especially when given to perpetrators of corruption who are considered to have caused massive losses to the state. In this context, this study aims to analyze whether granting remissions to corruption convicts is by human rights principles and how it impacts the government's efforts to eradicate corruption. This study uses a normative approach by analyzing applicable laws and regulations and empirical data related to the implementation of remission policies in Indonesia. The results indicate that although remissions are regulated for rehabilitation purposes, their application to corruption convicts needs to be more selective so as not to damage the main objectives of eradicating corruption and social justice.